Some Willowsia from Nepal and Vietnam (Collembola: Entomobryidae) and description of one new species - Zhang, Feng (Zootaxa, 2015)
Willowsia bartkei Stach, 1965 and W. pseudosocia Stach, 1965 from Vietnam are redescribed based on type material. Willowsia cassagnaui sp. nov. from Nepal is described here and is similar to another Nepalese species, W. ieti Yosii, 1971, but differs from the latter in colour pattern and mouthparts. Additions are given here to the original description of W. ieti.